Diethyl [(4-bromophenyl)(5-chloro-2-hydroxyanilino)methyl]phosphonate - Babu, V. H. H. Surendra (International Union of Crystallography, 2009)
In the title compound, C(17)H(20)BrClNO(4)P, intermolecular C—H⋯O and N—H⋯O hydrogen bonds form centrosymmetric R (2) (2)(10) dimers linked through O—H⋯O intermolecular hydrogen bonds, which form centrosymmetric R (2) (2)(16) dimers. All these hydrogen bonds form chains along [010]. In addition, the crystal structure is stabilized by weak C—H⋯Br hydrogen bonds. The very weak intramolecular N—H⋯O interaction forms a five-membered ring.